Featured Front Cover. (15th January 2023) - Pricope, Narcisa G.; Daldegan, Gabriel A.; Zvoleff, Alex; Mwenda, Kevin M.; Noon, Monica; Lopez‐Carr, David
Abstract : The cover image is based on the Research Article Operationalizing an integrative socio‐ecological framework in support of global monitoring of land degradation by Narcisa G. Pricope et al., https://doi.org/10.1002/ldr.4447 . Abstract : The cover image is based on the Research Article Operationalizing an integrative socio‐ecological framework in support of global monitoring of land degradation by Narcisa G. Pricope et al., https://doi.org/10.1002/ldr.4447 .